ARIA-ITALY multidisciplinary consensus on nasal polyposis and biological treatments - Carlo Lombardi, MD (Elsevier, 2021)
In the recent years, it was recognized that type-2 inflammation links many forms of nasal polyposis with severe asthma. Thus, some biological drugs developed for severe asthma appeared to exert an effect on nasal polyposis. So far, there are several trials supporting this concept; therefore, some monoclonal antibodies for severe asthma were assessed also in polyposis, with promising results. Since different specialists are involved in the management of nasal polyposis (eg, pulmonologists, ENT, allergists), it was felt that an educational and informative document was needed to better identify the indications of biologicals in nasal polyposis. We collected the main Italian Scientific Societies, and prepared (under the Allergic Rhinitis and its Impact on Asthma, ARIA) a document endorsed by all Societies, to provide a provisional statement for the future use of monoclonal antibodies as a medical treatment for polyposis. It is the first nationwide endorsed document on this aspect. The current pathogenic knowledge and the experimental evidence are herein reviewed, and some suggestions for a correct prescription and follow-up are provided.